Anti-inflammatory Natural Prenylated Phenolic Compounds - Potential Lead Substances - Brezani, Viliam; Smejkal, Karel; Hosek, Jan; Tomasova, Veronika (Current medicinal chemistry, 2018)
BACKGROUND: Natural phenolics are secondary plant metabolites, which can be divided into several categories with the common structural feature of phenolic hydroxyl. The biological activity of phenolics is often modified and enhanced by prenylation by prenyl and geranyl; higher terpenoid chains are rare. The type of prenyl connection and modification affects their biological activity. OBJECTIVE: This review summarizes information about prenylated phenols and some of their potential sources, and provides an overview of their anti-inflammatory potential in vitro and in vivo. METHOD: The literature search was performed using SciFinder and keywords prenyl, phenol, and inflammation. For individual compounds, an additional search was performed to find information about further activities and mechanisms of effects. RESULT: We summarized the effects of prenylated phenolics in vitro in cellular or biochemical systems on the production and release of inflammation-related cytokines; their effects on inhibition of cyclooxygenases and lipoxygenases; the effects on production of nitric oxide, antiradical and antioxidant activity; and the effect on the inhibition of the release of enzymes and mediators from neutrophils, mast cells and macrophages. The information about the antiphlogistic potential of prenylated phenolics is further supported by a review of their action in animal models. CONCLUSION: Almost 400 prenylated phenols were reviewed to overview their antiinflammatory effect. The bioactivity of several prenylated phenols was confirmed also using in vivo assays. A pool of natural prenylated phenols represents a source of inspiration for synthesis, and prenylated phenols as components of various medicinal plants used to combat inflammation could be their active principles.
Keywords: Plant Extracts; fenoly; rostlinné extrakty; Animals; vztahy mezi strukturou a aktivitou; antiflogistika; Molecular Structure; Phenols; léčivé rostliny; Prenylation; molekulární struktura; lidé; Structure-Activity Relationship; Plants, Medicinal; zvířata; prenylace; Anti-Inflammatory Agents; Humans